Who's in and Who's Out? Selection Bias in Aging Research. (16th December 2020) - Mayeda, Elizabeth Rose; Hayes-Larson, Eleanor; Banack, Hailey
Abstract: Selection bias presents a major threat to both internal and external validity in aging research. "Selection bias" refers to sample selection processes that lead to statistical associations in the study sample that are biased estimates of causal effects in the population of interest. These processes can lead to: (1) results that do not generalize to the population of interest (threat to external validity) or (2) biased effect estimates (associations that do not represent causal effects for any population, including the people in the sample; a threat to internal validity). In this presentation, we give an overview of selection bias in aging research. We will describe processes that can give rise to selection bias, highlight why they are particularly pervasive in this field, and present several examples of selection bias in aging research. We end with a brief summary of strategies to prevent and correct for selection bias in aging research.